7a+10b+6a-3b=

Simple and best practice solution for 7a+10b+6a-3b= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7a+10b+6a-3b= equation:


Simplifying
7a + 10b + 6a + -3b = 0

Reorder the terms:
7a + 6a + 10b + -3b = 0

Combine like terms: 7a + 6a = 13a
13a + 10b + -3b = 0

Combine like terms: 10b + -3b = 7b
13a + 7b = 0

Solving
13a + 7b = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-7b' to each side of the equation.
13a + 7b + -7b = 0 + -7b

Combine like terms: 7b + -7b = 0
13a + 0 = 0 + -7b
13a = 0 + -7b
Remove the zero:
13a = -7b

Divide each side by '13'.
a = -0.5384615385b

Simplifying
a = -0.5384615385b

See similar equations:

| -5+24x=23 | | 4=n+10 | | x+3=68 | | 7j+4j= | | 5x^4=5x | | 4f-8=-4n-12 | | 8+4(-8+3)=-12 | | 6+(n+7)2=25 | | (4x-16)=(2x+6) | | -6x=114 | | -4x-12y=12 | | 9u-2u= | | 7x-7=-5+2x-12 | | 6x+4=2(2x-5) | | 7c+5c= | | 1.5x-5=4x | | 2(2x-5)-3+2=x+9 | | b^3-4b^2=21b | | -16=(-x) | | 9f+2f= | | 7v+4v= | | -38-(-14)= | | ln(8-x)=ln(3x-2)+ln(x+2) | | -6z+8=-13 | | y=.66x-1.25 | | 1.5y-12=60 | | ln(8-x)=ln(3x-2)+ln(x-2) | | 8(3x-19)=15x+7 | | .5(4x+1)(3x)=27 | | -m+2n=3 | | 4-10.00+4=44 | | 0.04c=5 |

Equations solver categories